International economic law : text, cases and materials - Choukroune, Leila; Nedumpara, James J. (Cambridge : Cambridge University Press, 2022)
Reconciling all fields of international economic law (IEL) and creating bridges between disciplines in a conceptual as well as practical manner, this book stands out as the first modern, comprehensive international economic law textbook. Containing a technically solid yet critically rich body of knowledge that spans disciplines from trade law to investment, from trade finance to fisheries subsidies, from development to the digital economy and other new-age topics, the book offers the widest possible coverage of issues in current international economic law. Positioning IEL as a truly global practice, the comprehensive coverage includes various treaty texts, landmark cases and new materials, and is supplemented by case studies, real-life examples, exercises and illustrations. The case extracts and legal texts are selectively chosen, with careful editing and serious deliberation to engage modern law students. Mini chapters show examples of interdisciplinary interactions and provide a window into the future disciplines of international economic law.
Title from publisher's bibliographic system (viewed on 29 Jul 2021).
Keywords: elektronické knihy; electronic books; International economic relations; International finance -- Law and legislation; Foreign trade regulation